Literacy and Language Teaching and Learning With Interactive Whiteboards in Early Schooling. Issue 3 (15th September 2015) - Prinsloo, Mastin; Sasman, Felicity
Abstract : Research on education and technology has sometimes examined model rather than typical practices, and has thus presented an idealized notion of what such resources might offer to situated users in education. This article asks what happens when particular digital resources, designed for one purpose, or carrying particular expectations regarding their uses, encounter complex, detailed, situated forms of life that differ in particular ways from those anticipated in the design of the digital resources. The study is that of teachers' uses of interactive whiteboards (IWBs) in a low‐socioeconomic environment on the Cape Flats in South Africa, in a classroom comprised of both middle‐class and working‐class children who bring a mix of English, Afrikaans, and isiXhosa home language resources to their learning. We draw on orientations to the study of language as heteroglossic and networked, to literacy as situated social practices, and to communication as multimodal to argue that IWBs function in this context as boundary objects, with a high degree of interpretive flexibility in that they are weakly structured transcontextually, but strongly structured in local use. Rather than contributing to a transformation of language and literacy pedagogy, they get taken hold of and used by teachers to complement their pre‐existing pedagogical strategies.